ETIOLOGICAL PROFILE OF CHILDREN ADMITTED WITH FEVER WITHOUT FOCUS FOR LESS THAN 7 DAYS DURATION AT TERTIARY CARE CENTER - NAGAR, RAJENDRA PRASAD; NAGAR, TEENA; VERMA, MADHURIMA; SHARMA, RAKESH (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of the study was to know about the etiology of acute undifferentiated febrile illness (AUFI) or fever without focus in children admitted at tertiary care hospital. Methods: A study was conducted at medical college, Jhalawar, for a period of 3 months. Pediatric patients presenting with fever for less than or equal to 7 days duration without focus, who required hospitalization were included in this study. Results: A total of 200 children enrolled in study. Male-to-female ratio was 1.9:1. Mean age of children was 7.21±4.2 years. About 142 (71%) patients presented after 3 days of fever. Average duration of fever before admission was 4.62±1.78 days. The most common cause of fever of short duration (less than 7 days) was dengue fever 74 (37%) followed by malaria 58 (29%) and typhoid fever 36 (18%). About 26 (13%) patients had mixed infection. Out of 200 patients, 70 (35%) patients had splenomegaly, 66 (33%) had hepatomegaly, and 26 (13%) patients had both hepatosplenomegaly. Conclusion: The common etiology of AUFI with short duration in children was dengue, malaria, and typhoid. Vector control measures, drinking water supply, and sanitation should be improved to prevent vector-borne and water-borne diseases.